Acute dystonia associated with metoclopramide: a case presentation - Korkmaz, Sevda; Atmaca, Murad; Saglam, Sadullah (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2012)
Although the underlying neurochemical anomaly is not known, it has been implicated that the pathophysiology of dystonia may be associated with abnormal dopaminergic activity in basal ganglia. Although it is frequently seen with classical antipsychotics, some dopaminergic agents such as metoclopramide may cause this side effect. In this paper, we present a 17 years old woman under treatment with metoclopramide in therapeutic doses, who was referred to our hospital because of acute dystonia.
Metoklopramidle gelişen akut distoni: Bir olgu sunumu
Keywords: Acute dystonia; metoclopramide